The Characteristics of Conjunctivitis Patients at the Eye Hospital Makassar: A Recent Analysis of January – December 2023 Records - M, A Alya Amaliah; Maharani, Ratih Natasha; Akib, Marlyanti Nur Rahmah; Aulia, Nur; Hastiah, Hastiah; Sodiqah, Yani (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Conjunctivitis is an inflammation of the conjunctiva caused by viruses, bacteria, fungi, or allergies, with varying prevalence based on etiology, age, gender, and season. Objectives: This study aims to determine the characteristics of conjunctivitis patients at the Makassar Eye Hospital from January to December 2023. Methods: This research employed a descriptive method with a retrospective approach using patient medical record data. The study included 118 conjunctivitis patients as the sample. Results: The most affected age group was 18–65 years (72%), followed by children (16.9%) and the elderly over 65 years (11%). Conjunctivitis was more prevalent in females (60.2%) than males (39.8%). The most common etiology was allergy (39%), followed by bacterial (31.4%) and viral causes (29.7%). Allergic conjunctivitis was primarily treated with artificial tears (30.4%) and antihistamines. Bacterial conjunctivitis was mainly managed with a combination of antibiotics, steroids, and artificial tears (43.2%). Viral conjunctivitis was also most frequently treated with the same combination therapy (40%). Conclusions: Conjunctivitis is most prevalent among individuals of productive age (18–65 years) and more common in females. Allergic conjunctivitis is the most frequent type, with artificial tears being the primary treatment.